Effect of Light Intensity and Duration of Light on the Fecundity and Development of the Fruit Fly Bactrocera carambolae (Diptera: Tephritidae) - Bakti Prima Dewi (Central Research Institute For Agriculture, 2021)
The purpose of this study was to determine the effect of light intensity and duration of light on the fecundity and development of the B. carambolae fruit fly. The experiment was conducted at the Pest Laboratory, Department of Plant Pests and Diseases, Faculty of Agriculture, Brawijaya University, Malang from April to July 2008. This research consisted of two experiments, namely, (1). Effect of different light intensity and length of light on fecundity and longevity of B. carambolae fruit flies (2). Effect of different light intensity and duration of light on the development of B. carambolae fruit flies. Each experiment was arranged using a factorial Randomized Block Design (RBD) consisting of 2 factors, namely light intensity with 3 levels (100 lux, 2000 lux and 3000 lux) and light duration with 4 levels (10 hours light and 14 hours dark, 12 light and 12 hours dark, 14 hours light and 10 dark, 24 hours light and 24 hours dark). The results showed that the use of a light intensity of 2000 lux with a light duration of 12 hours of light and 12 hours of darkness had a good effect on the fecundity of the B.carambolae fruit fly by 80 eggs, while the developmental yield of B.carambolae fruit fly from hatching eggs was 51.33%, The duration of the larval stage was 10.17 days, the number of pupae formed was 61 eggs, the pupal weight was 0.012 g, the pupal stage was 9.39 days long, and the number of adults formed was 53 individuals, given a light intensity of 2000 lux with 12 hours of light and 12 hours of light. dark insects, hormone manipulation techniques, for the purposes of biological control as well as research on the physiology, ecology, genetics and biology of the fruit fly.